Assessment of the effects of development on drainage the case of the UP Diliman Engineering Complex - Manicad, Fernando Victor A. III; Herrera, Eugene C.; Lumbera, Maxell P. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
As the propulsion of urbanization in the global tier drives construction and development of rural lands into thriving urban cities, the need to assess its effects on all aspects of environmental health intensifies. This study focuses on the effects of urbanization on drainage and the natural hydrology over a land under considerable change in development or use. Urban flooding, in general, is usually caused by poorly planned global urbanization as seen in inefficient drainage systems. For this study, the specific case of the UP Diliman Engineering Complex was investigated for it is one of the areas in the campus currently undergoing a change in land use. Development and construction of new buildings, laboratories, and other facilities in a compound housing all engineering disciplines is underway in an area which previously had the characteristics of a rural area - less pavements, and more previous surfaces. Assessment of the drainage is done by first delineating the watershed in the area based from its natural topography using ArcGIS. Upon delineation, a model of the drainage system is set-up using SWMM. Simulations using rainfall events of Typhoons Ondoy (2009), Pedring (2011), and Habagat (2012) are done and results are tabulated and analyzed. Results show that for short-term rainfall events, the drainage capacity of the Engineering Complex is sufficient, however for long-term rainfall events flooding occurs in various points of the drainage as evidenced by actual site conditions. In the study area, three critical ponding locations are identified, namely, ICE, EEEI, and DChE, where an increase of 40%, 86%, and 89%, respectively, in the surface runoff produced from subcatchments is observed from the time before development took place in the area up to existing conditions. Velocities of flows in conduits reach a maximum of 2.45 m/s, with maximum flows in conduits attained at around 17 hours from peak rainfall.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Drainage; Flood forecasting